2015
DOI: 10.1093/humrep/dev073
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysfunction in obese Hispanic women with polycystic ovary syndrome

Abstract: This project was supported by the following National Institutes of Health grants: K23 DK080988-01A1 to S.S. and UL1RR029879 to CTSA at University of Illinois. None of the authors report any conflict of interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…A higher percentage of PCOS patients were in the category of large and extra-large circumference than was reported previously in women only having PCOS 19 . These results also supports the results of previous studies reporting that increased waist and hip circumferences increase the incidence of PCOS and associated complications involving infertility 24 …”
Section: Discussionsupporting
confidence: 90%
“…A higher percentage of PCOS patients were in the category of large and extra-large circumference than was reported previously in women only having PCOS 19 . These results also supports the results of previous studies reporting that increased waist and hip circumferences increase the incidence of PCOS and associated complications involving infertility 24 …”
Section: Discussionsupporting
confidence: 90%
“…In PCOS, smaller and denser LDL particles, which are more atherogenic, are more commonly found. 10,[14][15][16][17] As for total cholesterol, our study has also shown that, even in lean patients, there seems to be an increased level of total cholesterol. This is in agreement with a previous Danish study which has also found increased median values of total cholesterol in PCOS subjects.…”
Section: Resultssupporting
confidence: 71%
“…Table 6 summarizes the Pearson correlation coefficient where female testosterone and 25(OH)D are associated with a lower level of osteocalcin. Sam et al (2015) examined the level of hormones, namely 25(OH)D, PTH, and testosterone, in the increase of PCOS cases [ 81 ]. Previously, Glintborg et al (2006) evaluated the risk factors associated with the increase in the cases of PCOS [ 82 ].…”
Section: Discussionmentioning
confidence: 99%